Banjar Cultural Marriage Taboos and Analysis of the Prohibition of Marriage in Kitabun Nikah by Sheikh Muhammad Arsyad Al-Banjari - Firdaus, Zein; Marbawi, Muhammad; Afif, Muhammad Wildan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Marriage is a sunnatullah presented by Allah SWT for the survival of mankind on this earth. Taboo in Banjar culture is a prohibition that is carried out during a wedding procession or before the wedding takes place. In Islam, there is no law against this taboo. This study uses qualitative research with a library approach. The results of the study show that in the Book of Marriage written by Syekh Muhammad Arsyad Al-Banjari, there is no specific prohibition against cultural taboos that exist in Banjar society, but he only explains the prohibition of marriage in Islamic law, such as the prohibition against marrying women of the same lineage, breastfeeding and so on other.